Educating dengue hemorrhagic fever to Jumantik Cadres using mobile application for mosquito nest eradication - Kholis Ernawati; Indah Kurnianingsih; Nurmaya Nurmaya; Muhamad Fathurahman; Muchamad Rinaldy; Keysha Farach Dwikhanza; Putri Alfira; Salsabila Azmi Qatrunnada; Rifda Wulansari (University of Merdeka Malang, 2023)
Dengue Haemorrhagic Fever (DHF) cases are rising due to community efforts to eliminate mosquito nests. This impacts how people act. Community educators known as